2022
DOI: 10.1111/jgs.17791
|View full text |Cite
|
Sign up to set email alerts
|

“Is it time to stop driving?”: A randomized clinical trial of an online decision aid for older drivers

Abstract: Background Many older adults face the difficult decision of when to stop driving. We sought to test whether an online driving decision aid (DDA) would improve decision quality. Methods This prospective two‐arm randomized trial enrolled English‐speaking licensed drivers (age ≥70 years) without significant cognitive impairment but with ≥1 diagnosis associated with increased likelihood of driving cessation; all participants received primary care in clinics associated with study sites in three states. The interven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…The DCS is a 16-item scale assessing the decision quality, internal conflict, and values concordance towards a medical decision (O’Connor, 1993; O’Connor, 1995). For the AUTO study, we modified the DCS to assess the decision quality of study partner’s decision whether the driver should stop or continue driving (Betz et al, 2021, 2022). The DCS has a test-retest correlation of .81, with internal consistency ranging between .78 and .92 (O’Connor, 1995).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The DCS is a 16-item scale assessing the decision quality, internal conflict, and values concordance towards a medical decision (O’Connor, 1993; O’Connor, 1995). For the AUTO study, we modified the DCS to assess the decision quality of study partner’s decision whether the driver should stop or continue driving (Betz et al, 2021, 2022). The DCS has a test-retest correlation of .81, with internal consistency ranging between .78 and .92 (O’Connor, 1995).…”
Section: Methodsmentioning
confidence: 99%
“…Data for this analysis uses data from the Advancing Understanding of Transportation Options (AUTO) study, a multi-site, two-armed randomized controlled trial testing the efficacy of the driving decision aid ((Healthwise, 2016) for older adult drivers and their study partner, which included family members and friends (Betz et al, 2021, 2022). We found that the decision aid decreased decisional conflict and increased driving knowledge in older adult drivers (Betz et al, 2022). Prior analyses of the impact of the decision aid did not evaluate its influence on the study partner’s decisional conflict or how their decisional conflict was associated with the driver’s.…”
Section: Introductionmentioning
confidence: 99%